Peran Akuntansi Forensik Terhadap Skema Ponzi Di Indonesia - Fredy Wijaya Ciputra; Mohamad Djasuli (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
A ponzi scheme is an act of fraud in investments involving repeated interactions with more and more people. This mode of deception is all about building and maintaining each individual's trust. All Ponzi schemes end dramatically when the perpetrators fail to pay or there is suspicion that the scheme is exposed. The task of forensic accounting is the preparation of legal opinions in court (litigation). In addition, the role of the Forensic Accountant is also in the jurisdiction outside the court (non-litigation), for example formulating alternative dispute resolutions, preparing compensation calculations and trying to calculate the impact of terminating/violating agreements.